2002
DOI: 10.1046/j.1469-0705.2002.00832.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical vein blood volume flow rate and umbilical artery pulsatility as ‘venous–arterial index’ in the prediction of neonatal compromise

Abstract: Objective To assess the diagnostic power of the umbilical venous−arterial index (VAI) for the prediction of poor fetal outcome. Subjects and methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 18 publications
2
56
0
2
Order By: Relevance
“…The determination of the maximal vessel diameter has proven to be essential for the assessment of the umbilical vein blood volume flow rate in the second trimester [19]. In our study, filling in the color of the E-flow, the interior of the umbilical vein allowed an easy identification of the vessel walls and of the diameter of the vein.…”
Section: Couples Of Twinsmentioning
confidence: 94%
“…The determination of the maximal vessel diameter has proven to be essential for the assessment of the umbilical vein blood volume flow rate in the second trimester [19]. In our study, filling in the color of the E-flow, the interior of the umbilical vein allowed an easy identification of the vessel walls and of the diameter of the vein.…”
Section: Couples Of Twinsmentioning
confidence: 94%
“…In a recent publication, Tchirikov et al [8] demonstrated that the venous-arterial ratio was superior to isolated arterial (umbilical and uterine) Doppler in the prediction of neonatal adverse outcomes. This could be attributed the capacity of evaluating cardiac post-load through venous Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…Tchirikov et al [8] presented a venous-arterial ratio involving umbilical vein velocimetry and umbilical artery pulsatility index (UA PI). Using 100 ml/min/kg as their cut-off value, these authors had 85% sensibility and 15% false-positives in prediction of neonatal complications.…”
Section: Venous-arterial Doppler Ratios In Acidemiamentioning
confidence: 99%
“…At the beginning of these studies, umbilical venous blood flow velocity was estimated from the maximum values of the waveforms [40,41]. Soon after, Doppler intensity-weighted mean velocity measurements were introduced [43,44] and its accuracy was improved.…”
Section: Umbilical Venous Blood Flowmentioning
confidence: 99%
“…They reported that umbilical venous blood velocity changed during fetal breathing movement [39] (Figure 1). Umbilical venous blood flow velocity waveforms have been used for assessing blood volume of placental perfusion [40][41][42][43][44] because the flow velocity is usually constant and it is easy to estimate the diameter of the vessels. At the beginning of these studies, umbilical venous blood flow velocity was estimated from the maximum values of the waveforms [40,41].…”
Section: Umbilical Venous Blood Flowmentioning
confidence: 99%